Haknuk : orang kita = our people - Adam Kamel Mat Jaya; Muhammad Azli Shukri; Universiti Malaysia Pahang (Kuantan, Pahang : Universiti Malaysia Pahang, 2009)
Projek semaian kasih (sowing the seeds of love project) for the semai community at Kampung Kuala Boh, Cameron Highlands
Keywords: Indigenous peoples -- Pahang; Indigenous peoples -- Pahang -- Social conditions; Senoi (Malaysian people) -- Pahang